Length-Weight Relationships and Otolith-Based Growth Curves for Brushtooth Lizardfish off Taiwan With Observations of Region and Aging–Material Effects on Global Growth Estimates - Chang, Shui-Kai; Chou, Yuan-Tian; Hoyle, Simon D. (Frontiers in Marine Science, 2022)
Establishing appropriate aging procedures and growth models are two important steps for estimating reliable growth curves and in developing proper stock assessments. Lizardfishes have a strong influence on the structures of epibenthic communities and are important to the trawl fisheries of many coastal countries. For brushtooth lizardfish, Saurida undosquamis, the major species in the lizardfish catches of Taiwan, three issues were investigated. First, we used generalized additive models to explore factors (e.g., sex, data source, season) affecting the length-weight relationship (LWR), and to estimate suitable parameters. Second, we identified suitable procedures for otolith preparation (sagittal or transverse sections), validated the periodicity of ring increments using marginal increment analysis (MIA) with discussions of the appropriateness of the analysis, and determined the “best-fit” growth model via multi-model inference. Lastly, we compared growth estimates from this study with those published globally and developed an overview of global variation and the main associated variables through hierarchical cluster analysis and random forest modeling. Results suggested the following. (1) A suitable LWR for the stock was BW = 6.269 × 10-3 · FL3.144 for females and BW = 6.439 × 10-3 · FL3.144 for males. The allometric coefficient varied among samples and data sources and through the season. (2) Aging precision may be higher using transverse sections rather than sagittal sections. MIA indicates that otolith ring marks are formed annually during the active spawning season at the end of winter and the beginning of spring (from February). The Von Bertalanffy Growth Model was selected and the parameters (L∞, K, and t0) were: 46.4 cm, 0.12 year-1, and -2.12 year for sex-combined; 38.6 cm, 0.15 year-1, -2.06 year for males; and, 42.0 cm, 0.16 year-1, -1.53 year for females. (3) Globally, 86 sets of growth parameters were compiled from the literature. Region and aging material were the most important sources of variation in global estimates, which indicates the importance of using reliable aging material.